Flipped Virtual Classroom Learning Model for the Course Study Discourse Analysis in Translation - Andri Purwanto (Scope : Journal of English Language Teaching, 2020)
This study aims to explain the learning models of flipped virtual classroom that can be applied in virtual classrooms in discourse analysis in Translation courses. When teaching, the learning model is explained by using video as an appropriate and efficient choice pattern to achieve learning objectives.  Flipped virtual classroom is a learning model that transfers synchronous virtual classroom models to asynchronous virtual classroom models. The research method in this discourse analysis in Translation course was through literary sources. The purpose of the research is to provide information about virtual learning methods as a means of enhancing learning and language proficiency in Bahasa Indonesia combined with translation reflection theory.  The virtual learning model can be combined with variations of learning models such as: Problem-based Learning, Inquiry-based Learning, Project-based Learning, Research-based Learning.  In conclusion, through the choice of an asynchronous virtual classroom learning model and the application of discourse analysis in Translation as a reflection activity in translation, students are able to make a more detailed and deeper translation analysis.